1984
DOI: 10.1159/000145865
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Elastic System Fibers in Hyaline and Fibrous Cartilages of the Rat

Abstract: Rat hyaline and fibrous cartilages whose glycosaminoglycans had been removed by hyaluronidase digestion were studied by comparing the ultrastructural features with the observation of sections stained by selective methods for elastic system fibers under the light microscope. Except for the fibrous layer in the perichondrium of tracheal hyaline cartilage, where elastic fibers were found, no elastic fibers could be detected in the cartilages studied. However, cartilaginous tissues contained oxytalan and elaunin f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
3

Year Published

1987
1987
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 11 publications
1
20
0
3
Order By: Relevance
“…12). Furthermore, microfibrils and their integral component, fibrillin, appear to be considerably accumulated in the perichondrium (Cotta-Pereira et al, 1984;Fig. 6.…”
Section: Discussionmentioning
confidence: 99%
“…12). Furthermore, microfibrils and their integral component, fibrillin, appear to be considerably accumulated in the perichondrium (Cotta-Pereira et al, 1984;Fig. 6.…”
Section: Discussionmentioning
confidence: 99%
“…In the above-mentioned paper Montes et al [1984) reported that no elastic fibers could be detected by light or electron microscopy in connective tissue sheaths of the nerves studied; however, two elastic-related fibers, oxytalan and elaunin. were found to be contained in the nerves.…”
Section: Introductionmentioning
confidence: 87%
“…Although the presence of oxytalan fibers in the epi-and perineurium was reported by Fullmer as long ago as 1958. it was not until very recently [Montes et al, 1984] that an investigation of the presence of elastic system fibers in nerves (using a combination of the selective staining methods of light microscopy and the ultrastructural obser vation after tannic acid-glutaraldehyde fixation) was per formed. In the above-mentioned paper Montes et al [1984) reported that no elastic fibers could be detected by light or electron microscopy in connective tissue sheaths of the nerves studied; however, two elastic-related fibers, oxytalan and elaunin.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the mature elastic fibers (elastin), become responsible for elasticity and elastic retreat of the VUJ, and in turn, elaunin fibers assume the intermediary role between oxytalan and mature fibers, providing functional adaptation to VUJ, as previously described by Cotta-Pereira et al (1977, 1984 studying the skin, so the function of an elastic fiber complements the action of another and form in VUJ, a microfibril-elastin system, as already described by Ushiki, working as a distributor of uniform tension forces in the tissue, maintaining tissue resilience and adapting the site for urine flow.…”
Section: Discussionmentioning
confidence: 71%